THE ROLE OF ABDI DALEM IN IMPLEMENTING THE SEKATEN TRADITION IN 2019 - Haris Mustaqim Munandar (CV. Fahr Publishing, 2023)
The purpose of this study was to determine: (1) the process of becoming an Abdi Dalem, (2) the role of Abdi Dalem in the palace environment, (3) the involvement of Abdi Dalem Soldiers and Gamelan in the implementation of Sekaten. The method used in this research is historical with heuristic steps, source criticism, interpretation, and historiography. The results showed that (1) the process of becoming an Abdi Dalem through selection, must be able to speak Javanese well, polite in action, Indonesian citizen, at least 17-45 years old, (2) The role of Abdi Dalem in the Keraton environment is always involved in the implementation of Sekaten , being a guard and cultural supporter in the palace, (3) the involvement of Abdi Dalem Soldier and Gamelan in the implementation of Sekaten, Abdi Dalem Prajurit acting as a guard in the implementation of Miyos Dalem, Kundor Gongso while Abdi Dalem Gamelan prepares the completeness of Miyos Dalem and Kundor Gongso arts.